THE INFLUENCE OF SOCIAL EDUCATION ON ENVIRONMENTAL AWARENESS AMONG STUDENTS - Loso Judijanto; Sulistiani, Indah; Purike, Era; Novia Nelza; Marzuki Marzuki (Jurnal Ilmiah Edukatif, 2024)
This study examines the effect of social education on the level of environmental awareness among students. With the increasing urgency of global environmental issues, understanding the effectiveness of education in shaping pro-environmental attitudes and behaviours is crucial. The research method in this study uses the literature method. The results showed that an environment-based social education programme with increased student pro-environmental awareness and actions. Students involved in the programme demonstrated a deeper understanding of environmental issues, improved critical thinking skills in the context of environmental issues, and more active participation in environmental conservation activities. The findings emphasise the importance of integrating environmental education into the social education curriculum and highlight the crucial role of education in shaping an environmentally conscious generation. The implications of this study include recommendations for curriculum development and teaching strategies that can enhance the effectiveness of social education in building environmental awareness among students.